Vietnam : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
2017 was a bumper year of broad-based and non-inflationary growth. Reforms continued, including in the banking sector, privatizations and cuts in red tape. The momentum is expected to continue, aided by reforms, higher potential output, and the global recovery. However, economic distortions and capacity constraints remain, as do external and domestic risks and longer-term challenges. The strong economy provides an opportunity for additional reforms to boost investment, ensure durable growth and resilient balance sheets, and reduce the external surplus.